SILL PILLAR STABILITY ANALYSIS BASED ON DISCONTINUITY PLANE IN CROSSCUT 10.4 SOUTH CIURUG UNDERGROUND MINE, UBPE PONGKOR PT. ANTAM Tbk. - PUTRA ADHI LAKSANA (NIM : 12106014); Pembimbing : Dr. Ir. Budi Sulistianto, MT., M.
UBPE Pongkor PT. ANTAM, Tbk. has been mining Ciurug vein at two different levels which are level 500 and level 600 using overhand stoping cut and fill. This aim is to increase production capacity. Until now, mining in level 500 will reach sill pillar zone. This zone is ore zone at the top level 500 which is used to support and protect the mining activity beneath and activity in the upper level (level 600). Therefore, the optimization calculations needed to find thickness of sill pillar stability that mining activities can be performed optimally and maximize ore recovery. Sill pillar stability calculations carried out using numerical methods and empirical methods. Mechanical parameters of rock mass obtained from laboratory test results. Other parameters such as geometry stope, stope conditions, and muscular conditions obtained from the observations/measurements in the field. Then these parameters will be used in the calculation of empirical and numerical modeling with a distinct element method. Empirical calculations used for determine the rock mass conditions at the study sites, while the numerical model used for analyze the effect of discontinuity plane against general behavior of the rock mass.Classification of rock mass using RMR and Q-system. Based on the classification of RMR, rock mass classified into class III (Fair Rock) with the corrected RMR was 41. While the classification system of Q-value of 0.716 was obtained indicating that the rock mass rocks belong to very poor. Supporting recommendations of each classification is almost same that using rockbolt with spacing 1.5 m and thickness of shortcrete 100 mm. These result used as reference in numerical modeling and found that the supporting recommendations using split set with spacing 0.75 m x 0.75 m and wstrap with spacing 1.5 m. Numerical modeling also shows that mining can only be done at current elevation with thickness of pillar are 10.67 meters.